PENGARUH RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), UKURAN PERUSAHAAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR KOSMETIK TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2021 - Efiyah, Efiyah; Awaludin, Muryan (JURNAL MITRA MANAJEMEN, 2024)
The purpose of this study is to determine the effect of Return On Equity (ROE), Debt to Equity Ratio (DER, company size, and company growth on the Company's value in cosmetic sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2021. Secondary data collected from cosmetic sector manufacturing companies listed on the Indonesia Stock Exchange in 2016ï€2021 and journals from previous researchers. The method used is quantitative descriptive static method. The sample was determined based on the purposive sampling method, and obtained a sample of 6 companies with a total of 36 financial statement samples. The data used in this study is panel data (pooled data) which is a combination of time series data and cross section data. In this study for data processing using Eviews 9. The results of this partial study show that Return on equity has a positive and significant influence on company value (PBV), Debt to assets ratio has a positive and significant influence on company value (PBV), Company size has a positive and significant influence on company value (PBV), The company's growth has an insignificant negative influence on the company's value (PBV), Return on equity, debt to asset ratio, company size and the Company's growth simultaneously have a significant effect on the company's value (PBV) of 96.6543% while 3.3457% is influenced by other factors that are not studied by this study. Â Keywords: Return On Equity (ROE), Debt to Equity Ratio (DER), Company Size, Company Growth, Company Value